(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2011)
The boom of social participation in diverse nations of Latin America has forced substantial changes in the lawful regulations that norm the matter, as well as the growth of the channels through which groups of base could perform more effectively such participation. However, the perception by which the constituted power, mainly conformed by the state organisms, still prevails in governing the destiny of all who are part of the constituting power (the electors and the common citizens). This essay proposes to enhance equity as one of the main factors that tend to offer more fluency to the mentioned social participation, but also enhance the institutionalized development of the constituting power, or that seen, in a different manner, managed with a sense of injustice, such determining factor of democracy and participation, could transgress social peace and generate circumstances that could also make an attempt on governability. So it is precise to rescue the most genuine concept of equity in the context of democracy and social participation. Hence, in conclusion: the problems of governability in Venezuela respond to (in part) to the moderation of the legislative powers (National Assembly) and the executive power (President of the Republic) in determining who and how the citizen participation is performed, which is no longer a self-merit of the civil society and the organized communities, to become a communicational flow and eventually, a deliberating event, designed and ruled by such constituted powers.